Factors hindering grade 7 learners on the reading skills at Dilokong Circuit, Sekhukhune East District, Limpopo Province, South Africa - Mashabela, Patience Mokgatle (My University, 2024)
The purpose of the study was to investigate factors that hinder reading skills of Grade 7 learners at Dilokong Circuit. The study interacted with the participants directly in their natural setting, being at their school. A qualitative research approach was applied in the study, whereby thematic method was used for data analysis. Participants were purposively sampled from the school. The study sample comprised of 6 Grade 7 learners, also the 2 educators who teach Sepedi in the sampled grade. Data collection instruments used in this study include document analysis (learners’ written essays), semi-structured interviews and non-participant observations. The study revealed that both learners and educators experience challenges regarding reading skills. Most of the learners struggle with reading comprehension. Thus, the study recommends that schools should encourage learners to read more books in order to have good understanding of written texts.
Thesis (M.Ed. (Language Education)) -- University of Limpopo, 2024
Keywords: Reading skills; Reading comprehension; Challenge regarding reading; Reading comprehension -- Ability testing; Reading Skills Competency Tests; Northern Sotho language -- Study and teaching -- South Africa -- Limpopo